Exploring the paradox of Muslim advantage in undernutrition among under-5 children in India: a decomposition analysis - Shreya Banerjee; Shirisha P. (BMC, 2023)
Abstract Background While there is a substantial body of research on inequalities in child nutrition along the axes of gender and socioeconomic gradient, the socio-religious differences in health and nutrition outcomes remain grossly understudied. The handful of studies on the socio-religious differential in child health outcomes has found a Muslim advantage in chances of survival and nutritional status over Hindus despite their comparatively lower socioeconomic status, which undeniably warrants investigating the pathways through which this paradoxical Muslim advantage manifests. Methods Using data from the National Family Health Survey, 2015-16, we quantify the inter-group differentials in child undernutrition (stunting, wasting, and underweight) between Muslims and caste-disaggregated Hindus. We further decompose the gap to delineate its major contributory factors by employing Fairlie's decomposition method. Results The analysis revealed that, compared to the Hindus as an aggregated group, Muslims have a higher rate of stunting and lower rates of wasting and being underweight. However, the differences get altered when we disaggregate the Hindus into high and low castes. Muslims have a lower prevalence of all three measures of undernutrition than the low-caste Hindus and a higher prevalence of stunting and underweight than the high-caste Hindus, consistent with their levels of socioeconomic status. However, the prevalence of wasting among Muslim children is lower than among high-caste Hindus. This nutritional advantage is paradoxical because Muslims' relatively poorer socioeconomic status compared to high-caste Hindus should have disadvantaged them. In the decomposition analysis, the Muslim advantage over the low-caste Hindus could only be partially attributed to the former's better economic status and access to sanitation. Moreover, the poor performance of Muslim children compared to the high-caste Hindus in stunting and underweight could mainly be explained by the religious differentials in birth order, mother's education, and wealth index. However, Muslim children's comparatively better performance in wasting than the high-caste Hindus remained a puzzle. Conclusion The Muslim advantage over high-caste Hindus in wasting and low-caste Hindus in all the indicators of undernutrition may have been rendered by certain 'unobserved' behavioural and cultural differences. However, further exploration is needed to make a definitive claim in this respect.